2002
DOI: 10.1128/jvi.76.22.11209-11215.2002
|View full text |Cite
|
Sign up to set email alerts
|

A Transactivator Function of Cottontail Rabbit Papillomavirus E2 Is Essential for Tumor Induction in Rabbits

Abstract: Infection of domestic rabbits with cottontail rabbit papillomavirus (CRPV) causes local papillomas which progress to carcinomas in more than 80% of cases. This animal model system therefore allows the identification of molecular mechanisms required for the induction and progression of epithelial tumors. The viral E2 protein stimulates both viral DNA replication and transcription, and these functions can be genetically separated. We introduced the respective mutations into CRPV E2 and found, in line with publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 48 publications
3
43
0
Order By: Relevance
“…This characteristic, therefore, allows papillomavirus DNA mutants to be studied in vivo, something that cannot be done in other animal models to date. However, different CRPV DNA challenge methods have been used in different laboratories (Brandsma et al 1991;Jeckel et al 2002;Kreider et al 1995;Lin et al 1993;Nonnenmacher et al 2006;Salmon et al 1997;Salmon et al 2000). Some delivery methods are more efficient than others and these outcomes complicate the interpretation of results obtained in the different laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic, therefore, allows papillomavirus DNA mutants to be studied in vivo, something that cannot be done in other animal models to date. However, different CRPV DNA challenge methods have been used in different laboratories (Brandsma et al 1991;Jeckel et al 2002;Kreider et al 1995;Lin et al 1993;Nonnenmacher et al 2006;Salmon et al 1997;Salmon et al 2000). Some delivery methods are more efficient than others and these outcomes complicate the interpretation of results obtained in the different laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…The E2 protein of the Cottontail rabbit papilloma virus (CRPV) has previously been demonstrated to play a major role in the development of CRPV dependent skin carcinogenesis (14). This is particularly interesting in light of our recently reported finding that the E2 protein of CRPV (15) has the ability to activate the in vitro expression of matrix metalloproteinase 9 (MMP-9), a protein involved in the degradation and remodelling of the extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 70%
“…4A). We decided not to delete the NES found in HPV16 E2, because the position in the N-terminal domain is within the transactivation domain of the protein with the consecutive risk of false-positive results (14). Using immunofluorescence and the eGFP-tagged E2 mutants, the localisation of the mutant proteins was determined.…”
Section: Resultsmentioning
confidence: 99%
“…Infections of New Zealand White rabbits with CRPV DNA were performed as previously described (10). Tumor numbers and the maximum diameter of each tumor were determined over a period of 5 months.…”
Section: Animal Modelmentioning
confidence: 99%
“…A causative relationship between β-HPV infection and nonmelanoma skin cancer development in immunocompetent individuals is suggested by epidemiologic data and by the fact that the associated risk factors (age, UV-mediated local immunosuppression, and transplantation-related immunosuppression) point to an infectious agent, most probably belonging to the β2 group, which includes HPV38 (8,9). An excellent animal model to study papillomavirusinduced skin cancer formation is the New Zealand White rabbit, in which infections with cottontail rabbit papillomavirus (CRPV) causes the development of tumors within 3 to 6 weeks postinfection, progressing within 6 to 12 months into invasive cancer without additional cofactors (10,11). Recently, we reported that the CRPV oncoproteins E6 and E7 are able to immortalize primary rabbit keratinocytes (12), a common feature of all carcinogenic HPV types (13), which is believed to be a key requirement for cancer formation.…”
Section: Introductionmentioning
confidence: 99%